EFL IN HEALTH PROMOTION CONTEXT: A NEEDS ANALYSIS APPROACH - Titis Dewi; Anwar Efendi; Song Cheen (UIN Siber Syekh Nurjati Cirebon, 2026)
The learning of English as a Foreign Language (EFL) plays a crucial role in professional fields such as health promotion. This study investigates the EFL writing needs of health promotion students to enhance their professional competence. Conducted with 274 students from a public university, a health polytechnic, and a College of Health Sciences in Yogyakarta, Indonesia, the research employed a mixed-methods approach using semi-open questionnaires and semi-structured interviews. The analysis focused on both target needs (specific language requirements) and learning needs (pedagogical strategies to bridge proficiency gaps).Findings indicate that 42% of students aim to use English to promote health through media, highlighting the importance of productive skills, particularly writing and speaking. Major challenges include limited vocabulary (25%) and insufficient grammar knowledge (22%), compounded by a curriculum that emphasizes speaking more than writing. Students prefer interactive and collaborative learning methods, such as group discussions (45%) and feedback (21%). They also favor structured writing processes, including brainstorming, drafting, and revising (21%), and practical multimedia resources, especially videos (33%). Thematic content related to health and sports (52%) and comprehensive assessment covering both process and product (87%) are highly valued.Qualitative findings reveal that students view English as essential for producing public health materials such as posters, pamphlets, and digital content. However, limited writing practice and reliance on translation tools remain concerns. Overall, the study underscores the need for a balanced, contextualized, and technology-integrated EFL curriculum that strengthens writing skills and supports students’ academic and professional development.